STUDENT PERCEPTION AND PROMOTION MIX OF HOUSEKEEPING DEPARTMENT AT TRISAKTI TOURISM INSTITUTE - Anis Darsiah; Dian Octarina; Vienna Artina Sembiring (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of student perceptions and promotion mix on the decision of Trisakti Tourism Institute students to choose the Housekeeping Department. This type of research is descriptive quantitative with multiple regression analysis methods. The population in this study were all students of the Trisakti Tourism Institute. While the sample in the study amounted to 133 respondents using the accidental sampling technique distributing questionnaires with a Likert scale of 1 to 5. Based on the results of the discussion above, it can be concluded that students' perceptions of the housekeeping departments are good with an average score of 3.73. This is of particular concern to the lecturers to maintain the quality of the teaching and learning process, especially so that students are more interested in working in the household world. Showing that advertising, personal selling, sales promotion, and public relations have a significant effect on the decision to choose a major in college